Palladium-catalyzed asymmetric three-component reaction between glyoxylic acid, sulfonamides and arylboronic acids for the synthesis of α-arylglycine derivatives - Jakob, Bastian; Diehl, Andreas M.; Horst, Kathrin; Kelm, Harald; Manolikakes, Georg (Frontiers in Chemistry, 2023)
A palladium-catalyzed asymmetric three-component synthesis of α-arylglycine derivatives starting from glyoxylic acid, sulfonamides and arylboronic acids is reported. This novel, operationally simple method offers access to the α-arylglycine scaffold in good yields and enantioselectivities. The utilization of α tailored catalyst system enables the enantioselective synthesis of the desired α-arylglycines despite a fast racemic background reaction. The obtained products can be directly employed as building blocks in peptide synthesis.